Proses Upaya Pelatihan Bahasa Korea di Lembaga Pelatihan Kerja Global Desa Bocoran Purwokerto: Penelitian - Fadilla, Nadia Nur; Alyarahma, Nur Shabrina; Faoziyah, Mailan; Astriana, Sandra Bella (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This investigate points to portray: 1) the Korean dialect preparing prepare at LPK Global Purwokwrto, and 2) the components that impact preparing. This inquire about employments a subjective approach. Information collection methods were carried out by implies of interviews, perception and documentation. Information legitimacy procedures utilize triangulation of sources and strategies. Information examination procedures in inquire about are information collection, information decrease, information introduction, and drawing conclusions. The comes about of this investigate are 1) the Korean dialect preparing prepare atLPK Global Purwokwrto : pointed at making a difference individuals who need to work in Korea with Korean dialect and culture preparing so they can pass the EPS-Topic exam and work in Korea. Preparing keeps going 3-4 months. Preparing fabric is fabric from modules and content books. The strategy utilized is adjusted to the fabric displayed, separated from that the strategy utilized is additionally the address strategy. The media utilized bolsters the preparing prepare. Assessment is carried out utilizing summative assessment and developmental assessment. 2) Components that impact the preparing prepare are preparing obstructions, understudy inspiration, and the quality of tutors/instructors.